Audit Quality: The Impact of Expertise, Independence and Ethics of Professional Accountant A Crosssectional Study - Adam Ramdani (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2021)
This study aims to determine the effect of expertise, independence, and ethics on audit quality at the Inspectorate of West Java Province. The study in the initial review of this study found that the audit quality is shown in the opinion given by the examiner, including the opinion